2004
DOI: 10.1111/j.1365-2982.2004.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclooxygenase‐2 inhibitors on gastric emptying and small intestinal transit in humans

Abstract: Endogenous prostaglandins regulate smooth muscle activity; prostaglandins and cyclooxygenase (COX) inhibitors influence gastrointestinal motility in inflammatory states such as postoperative ileus in animal models. The objective of this study was to evaluate the effects of two COX-2 inhibitors on gastric emptying and intestinal transit in healthy humans. In a double-blind, placebo-controlled, parallel-group study, 66 healthy volunteers were randomized to one of two commercially available oral COX-2 inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
2
28
1
Order By: Relevance
“…The involvement of formation of PGE-2 in the gastroprotective mechanisms was previously investigated with conflicting evidences [25], [29], [33], [34]. PGE-2, the most abundant GI prostaglandin, is fundamentally important in the regulation of gastric mucus secretion [78], gastric acid secretion [79] and gastric motility [80], [81]. In oral administration of ethanol, reduction in formation of PGE-2 lessened acid secretion and gastric motility [78], and decreased gastric mucus secretion [82].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of formation of PGE-2 in the gastroprotective mechanisms was previously investigated with conflicting evidences [25], [29], [33], [34]. PGE-2, the most abundant GI prostaglandin, is fundamentally important in the regulation of gastric mucus secretion [78], gastric acid secretion [79] and gastric motility [80], [81]. In oral administration of ethanol, reduction in formation of PGE-2 lessened acid secretion and gastric motility [78], and decreased gastric mucus secretion [82].…”
Section: Discussionmentioning
confidence: 99%
“…Those studies that have shown a benefi t in using COX-2 inhibitors have not been able to demonstrate that the reduction in POI is independent of the subsequent reduction in opioid use. The main benefi t of these drugs has been their ability to lower the total dose of narcotics needed for adequate pain control (Bouras et al 2004;Sim et al 2007). Similar trials have occurred using the intravenous anti-infl ammatory drug, ketorolac.…”
Section: Nsaidsmentioning
confidence: 93%
“…Correspondingly, 52 subject groups were included within the analysis. The analysis included 11 investigations (Davis et al, 1984a(Davis et al, ,b, 1986a(Davis et al, , 1987Khosla et al, 1989;Madsen and Jensen, 1989;Coupe et al, 1991;Madsen, 1992;Billa et al, 2000;Bouras et al, 2004;Fadda et al, 2009), where estimates of intestinal transit were pooled between test conditions (e.g., fasted versus fed). For each of these investigations, mean intestinal transit times were not found to be significantly different between treatment arms as either denoted by the authors' results or independently confirmed using a paired Student's t test (P .…”
Section: Resultsmentioning
confidence: 99%